Finite element analysis of HDPE/EPR-CNT nanocomposite under tensile loading - Shaffiar, Norhashimah; Hasnan, M.A.; Anuar, Hazleen; Al Hazza, Muataz Hazza Faizi (2015)
A small amount of nano dispersed filler leads to an improvement in material properties. Carbon Nanotube (CNT) is one type of filler used in nanocomposite material. A high density polyethylene/ethylene propylene rubber – carbon nanotube (HDPE/EPR-CNT) is one of the nanocomposite material that is new to the industry. This paper investigates the strength of HDPE/EPR-CNT nanocomposite under tensile loading. The experimental results of the tensile test on the nanocomposite will be compared with the tensile simulation in the Finite Element (FE) analysis for validation. The results showed that it is validated with relatively low percentage error of 0.14 % for the ultimate tensile strength and 0.05 % for the yield strength. The ultimate tensile strength of HDPE/EPR-CNT is 17.41 MPa and the yield strength is 14.9 MPa. By using CNT as a filler, the material strength is improved. The ultimate tensile strength of HDPE/EPR-CNT is the highest compared to polyethylene/ethylene propylene rubber - montmorillonite HDPE/EPR-MMT and polyethylene/ethylene propylene rubber HDPE/EPR.